Estudio de prefactibilidad para la instalación de una planta de producción de hojuelas a base del bagazo cervecero - Arribasplata Caballero, Cynthia Allison (2022)
The present project is a pre-feasibility study for the installation of a brewers' bagasse-based flakes production plant that will analyze the market, technological and economic-financial viability of the brewers' bagasse. This product is beneficial to consumers due to its dietary fiber content. A diet rich in fiber is known to prevent obesity (Kyrø et al., 2011), reduce the risk of certain diseases, such as type 2 diabetes (Pan et al., 2010), cardiovascular diseases (Mellen et al., 2008), and certain cancers of the digestive tract (Fardet, 2013). The demand for the project has been calculated using Euromonitor International databases as a reference. It has been segmented geographically in Metropolitan Lima, with consumers between 25 and 55 years of age and socioeconomically in levels A, B, and C. Subsequently, to capture the market, 8% has been considered to obtain the final demand of the project. Finally, the demand in the last year of the project will be 409 649 bags of 100 grams. The location of the proposed plant is in the district of Ate, Lima. This district offers several industrial premises for purchase and lease. It also stands out from the other districts because of its proximity to the raw material supplier, which is reflected in savings in logistics costs. To define the production process for bagasse flakes, semi-automatic technology was selected as the most appropriate because it is a food product. Also, the production plant was designed based on the Guerchet analysis and the relational diagram. Finally, the economic and financial analysis of the project was carried out, obtaining a financial IRR of 56%, which is higher than the COK 27%, demonstrating that the project is profitable. On the other hand, since the financial NPV is S/ 543 926,70 it reaffirms the viability of the project.